Metadata quality of 3D models from Sulaymaniyah - Sáenz Santos, Luis Daniel; Bauer, Steffen; Gordin, Shai (Universität, 2025)
This dataset contains metadata for 3D models hosted in heidICON, specifically from the pool "Keilschrifttafeln aus Sulaymaniyah". It includes a standalone CSV ( Slemani_3D-Modelle_Metadaten.csv) file with consolidated metadata for all models, as well as a ZIP archive (Slemani_3D-Modelle_Metadaten_einzeln.zip) containing separate CSV files for each individual model. The metadata provides information about the 3D meshes and their quality.